MEMBACA PERSEPSI, MENAKAR PROSPEK: SEBUAH CATATAN REFLEKTIF TENTANG ULAMA DAN PEMBERDAYAAN PEREMPUAN DI LOMBOK - Umam, Fawaizul (EGALITA, 2007)
In the growing debate on gender discourse, religious texts (normative doctrines) is one of primary bases of producing and reproducing theological arguments for the debate particularly on the issue of gender relation in society. Then, religious figures (Ulama) whoÂ  pose the â€œauthorityâ€ to interpret the text and to build social and religious assumptions (from the texts) on gender issues which influence the prospect and the feature of women empowerment in society become one influential factors for gender equality realization. Therefore, Ulama play significant role in determining social perception on gender in the religious-cultural level of society.